Membangun Masyarakat Partisipatif: Dinamika Partisipasi Perkumpulan Pagar Madani dalam Perumusan Kebijakan Anggaran di Ngawi - Syamsul Wathoni (MUHARRIK: Jurnal Dakwah dan Sosial, 2018)
Independent community associations are important means so that civil society can develop and its institutions are strengthened. Both will be important for strengthening and empowering communities at the local level where they can ensure that decisions are made from the bottom without coercion and intervention from above. Community empowerment is also carried out so that the community is able to control the policies that have been taken in a participatory manner. Empowerment is also carried out to dismantle the silent culture and false consciousness that has long been upon Indonesian society. In Ngawi District, the movement of groups of citizens who participated in budget policy began to bloom. The birth of various active citizen groups with various interests also contributes to the public sphere of policy in Ngawi Regency. One such group of people is the Pagar Madani Association, which is a combination of various community groups, professional groups and active individuals. This association was born from the awareness of various community groups in Ngawi who realized that their participation in the budget policy agenda in Ngawi Regency was very important to realize the regional budget that was pro-poor. Their direct involvement in the budget planning process, endorsement, implementation and evaluation will be able to influence the results of public policies formulated by the Regional Government and DPRD. From the background above, encourages the writer to know more about the dynamics of community participation in the budgeting process in Ngawi District. This research is considered important, to determine the dynamics of the participation of community groups in Ngawi District, especially the Pagar Madani Association in relation to the formulation of regional budget policies.